2023
DOI: 10.3390/polym15061430
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Antimicrobial and Antitumoral Activities of Naphthoquinone-Grafted Chitosans

Abstract: Biopolymers obtained from natural macromolecules are noteworthy among materials presenting high biocompatibility and adequate biodegradability, as is the case of chitosan (CS), making this biopolymeric compound a suitable drug delivery system. Herein, chemically-modified CS were synthetized using 2,3-dichloro-1,4-naphthoquinone (1,4-NQ) and the sodium salt of 1,2-naphthoquinone-4-sulfonic acid (1,2-NQ), producing 1,4-NQ-CS and 1,2-NQ-CS by three different methods, employing an ethanol and water mixture (EtOH:H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Among these compounds, chitosan and its several derivatives, such as hydrogel, sponge, film, scaffold, nanoparticle, sulfate or sulfonated-chitosan, among others, can have a positive effect on wound healing. Chitosan is able to interfere in the first three stages; hemostasis, inflammation, proliferation and migration, accelerating wound closure as demonstrated by the migration assay ( Matica et al, 2019 ; Feng et al, 2021 ; Ferreira et al, 2022 ; Pauli et al, 2023b ; Ferreira et al, 2023 ) ( Figure 8 , panels A–B). It has been reported that chitosan promotes blood clot formation by stimulating the expression of the adhesion molecule GP IIb-IIIa at the surface of activated platelets and by stimulating platelet aggregation via electrostatic interactions between positively charged chitosan and negatively charged molecules at the surface of activated platelets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these compounds, chitosan and its several derivatives, such as hydrogel, sponge, film, scaffold, nanoparticle, sulfate or sulfonated-chitosan, among others, can have a positive effect on wound healing. Chitosan is able to interfere in the first three stages; hemostasis, inflammation, proliferation and migration, accelerating wound closure as demonstrated by the migration assay ( Matica et al, 2019 ; Feng et al, 2021 ; Ferreira et al, 2022 ; Pauli et al, 2023b ; Ferreira et al, 2023 ) ( Figure 8 , panels A–B). It has been reported that chitosan promotes blood clot formation by stimulating the expression of the adhesion molecule GP IIb-IIIa at the surface of activated platelets and by stimulating platelet aggregation via electrostatic interactions between positively charged chitosan and negatively charged molecules at the surface of activated platelets.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, chitosan exerts anti-inflammatory effects that reduce inflammatory cytokines, IL-10 and TNF-α, reducing oxidative damage and inflammation ( Yang et al, 2016 ; Mohyuddin et al, 2021 ). However, as mentioned above, antimicrobial effectiveness depends on a variety of intrinsic and extrinsic factors ( Matica et al, 2019 ; Feng et al, 2021 ; Ferreira et al, 2022 ; Pauli et al, 2023b ; Ferreira et al, 2023 ). Moreover, chitosan can stimulate the proliferation of fibroblasts, which compose the remodeled tissue during wound healing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that inserting sulfanyl, alkoxy, and/or amino group(s) into the quinone moiety improves its physical, chemical, and biological properties (Ibacache et al, 2016; Ibis et al, 2011; Kadela et al, 2016; Nagar & Dhar, 2022). Reactions between 1,4‐quinones and amines that address biologically important lead molecules have been extensively reported (Lima et al, 2021; Lopez‐Lira et al, 2021; Pauli et al, 2023; Uysal et al, 2021; Varricchio et al, 2020; Yildirim et al, 2022). In line with these studies, we investigated halogenated (brominated and chlorinated) and non‐halogenated plastoquinone (PQ) analogs to understand their antiproliferative profiles against breast cancer cell lines (Jannuzzi et al, 2021, 2022; Yilmaz Goler et al, 2022).…”
Section: Resultsmentioning
confidence: 99%